PROBLEM BASED LEARNING MODEL WITH AUGMENTED REALITY MEDIA ENCOURAGES CLASS V SCIENCE LEARNING ACHIEVEMENT - Angelina Sepfi Yolansari; Rusnilawati Rusnilawati (Jurnal Cakrawala Pendas, 2025)
Research on science learning achievement is still not optimal due to the low use of IT media. Apart from that, students are still not used to applying science concepts to everyday life problems. Data collection techniques in this research used pre-test and post-test methods, using multiple choice questions and essays. This research aims to test the impact of the Problem Based Learning model integrated with augmented reality media on the academic performance of class V students. The research carried out utilized quantitative methods with a quasi-experimental design or non-equivalent control group design. The research sample was class V students at Nusukan Elementary School with 28 experimental group students and 28 control group students. The research instrument is in the form of multiple choice questions and essays through validity and reliability tests. The research results show that there is a significant difference between the post-test results for the experimental class, namely 93 and the post-test results for the control class, namely 71. This can be shown from the results of the N-Gain test analysis in the experimental class, which was 85.15% and in the control class, which was 63. .99%. Based on the results of the independent t-test, there are significant differences in the experimental class and control class on student learning achievement. The research results show that augmented reality media is very helpful in the problem orientation step because it is able to encourage students to understand and find solutions to problems or challenges.